Analisis Kinerja Pegawai Pada Dinas Tenaga Kerja dan Transmigrasi Karawang - Siti Dita Pratiwi; Uus Mohammad Darul Fadli (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
The labor and transmigration office is a government agency in regulating the placement of workers in various regions. The aim is to optimize the utilization of human resources according to the needs of a particular region. Employee performance in a company is the main element of human resources, human resources work as the driving force of the organization both in institutions and companies, which has a function as an asset so that it must be trained and developed its capabilities. and has a very important role in determining the success of the organizers of a company. And this research design is qualitative research, qualitative research is research that produces descriptive, the research place is at the Manpower and Transmigration Office located on Jl. Surotokunto Warungbambu, Kec. Karawang Tim., Karawang. The results of interviews regarding employee performance can be concluded that employee performance assessment can be seen from individual employees at the labor and transmigration office.